Communication channels used by academic staff in interacting with their students - Baghestan, Abbas Ghanbari; Zavareh, Mehrnoosh Akhtari; Abu Hassan, Musa (Universiti Putra Malaysia Press, 2009)
The aim of this paper is to report the findings on the impact of communication technology as a channel for interaction between academic staff and their students, conducted at a Malaysian higher learning institution. The study focused on media choice and it attempted to determine the communication channels mostly used by academic staff in interacting with their students and the reasons for selecting these channels. It also intended to find out whether there was a significant relationship between communication channels mostly used by academic staff and their perception of media richness. The results revealed that although the existence of new communication technologies such as the internet offers faster and cheaper facilities, face-to-face communication is still the most used and preferred communication channel by academic staff in interacting with their students. In addition, there was a significant relationship between the communication channel mostly used by respondents and their perception of media richness and social presence. This explained why the higher level of social presence, the higher the level of experience with a channel would be. The findings of this study extended two of the most widely investigated media choice theories; Media Richness Theory (MRT) and Social Presence Theory (SPT).